Handlungskoordination in der Lernwelt Hochschule Rahmenbedingungen kompetenzorientierter Lehre - Becker, Alexandra (Lernwelten, 2022)
The switch from teaching to learning, competence-based teaching, and new public management are calling for changes to be made to the way that activities are coordinated at universities. Educational governance can help to meet these requirements, but additional, competence- and student-oriented perspectives are required. This volume thus provides a theoretical basis for implementing the necessary changes in university management.